Environmental Effects on Post-CMP PVAc Brush Releasable Contamination and Break-In Optimization for Advanced Logic and Memory Technologies. (6th December 2019) - Withers, Bradley; Hughes, Corey; Luo, Yuyan; Chen, Henry; Nelson, Erik; Best, Brent; Jeon, Jang Hun
Abstract : Advanced sub-7nm logic and VNAND memory technologies are becoming more reliant on Chemical Mechanical Planarization (CMP). New layers and materials are being introduced with each new technology node and integration scheme. Polyvinyl-acetal (PVAc) brushes are used extensively for post-CMP contact cleaning and remain the most reliable method for efficient cleaning of slurry residues while minimizing physical damage to sensitive films and structures. The releasable contamination from the virgin PVAc brush, however, is becoming more of an issue with each new technology node often affecting the yield of the device being manufactured. As a result, users are required to "break-in" or pre-condition brushes much longer than before to meet the required defect performance for these technologies. Longer PVAc brush break-in times negatively impact CMP tool utilization and overall equipment efficiency (OEE). This work attempts to characterize PVAc brush releasable contamination sources under simulated post-CMP cleaning conditions and suggests ways to reduce the break-in burden. Liquid particles (LPCs) were analyzed in the brush effluent and samples were subsequently dried and characterized by Fourier-transform infrared spectroscopy (FTIR). Environmental effects such as brush handling, temperature cycling, and dehydration, as well as post-CMP chemistry acclimation were all deemed significant contributors to the final releasable contamination profile and break-in characteristics of the brush. The brush Pore Templating Agent (PTA) represented the largest contribution of particles early in the brush lifetime. Loose PVAc particles were also a significant source of brush releasable contamination. PTA residue appears to decreases rapidly during brush use, whereas PVAc particulates reduce at a slower rate and eventually become the primary source of liquid particles. The physical nature of the post-CMP process and surface changes observed on the brush nodule are evidence that PVAc particulate reduction is largely unavoidable. PVAc brush break-in times, nevertheless, were accelerated by more aggressive break-in conditions and the application of chemistries known to improve the hydrolysis and removal of PTA. Offline but onsite PVAc brush break-in may be the most effective way to recover CMP tool utilization while minimizing environmental and chemistry acclimation effects simultaneously.